Analisis Berpikir Kritis Siswa dengan Self Confidence Tinggi pada Materi Bangun Datar - Febriani, Indri Rohmatul Fakhri; Rahaju, Endah Budi (MATHEdunesa, 2024)
This study is descriptive qualitative research that aims to describe the critical thinking of high self-confidence student on plane figure material. The research subject was eighth grade student consisting of one student with high self confidence. The research results show that student with high self-confidence are complex in evaluating problems. At the interpretation stage, student can explain problems, create illustrations, at the analysis stage student can identify each statements so they can find a solution. At the evaluation stage, student checks and assess the truth of the statement. At the inference stage student can show alternative answers and make conclusions. At the explanation stage, student can explain the steps and provide reasons based on the results obtained coherently. At the self regulation stage, student can review or explain the solutions that student have made both in writing and verbally and student are confident in the solutions that student have made.